Effect of Pinus patula (Panacea) plantations on soil and vegetation in the Rabanal moor, Samacá Boyacá: Efecto de las plantaciones de Pinus patula (Pinaceae) sobre suelo y vegetación en el páramo de Rabanal, Samacá Boyacá. (BISTUA Revista de la Facultad de Ciencias Básicas, 2024)
The Rabanal moor covers 4,172 hectares, of which 16% corresponds to the municipality of Samacá, it has two reservoirs, a dam for storage and regulation of water and pine plantations that generate the immobilization of nutrients, the reduction of the capacity to carry out recycling processes, and soil acidification. The objective of this study is to evaluate the effect of Pinus patula plantations on the soil and vegetation of the Rabanal páramo in the municipality of Samacá-Boyacá. Taking into account the vegetation of the moor and the plantation in terms of height, coverage, frequency and DBH of the species. In the paramo, 16 families, 35 genera and 42 species were recorded, in 501 individuals, the most abundant species were Espeletia boyacensis, Paepalanthus alpinus, Arcytophyllum nitidum and Puya nitida, versus the paramo planted with P. patula where 6 families were recorded, 6 genera and 6 species, with 80 individuals. Regarding the soil, the variables that presented significant differences were calcium, magnesium, magnesium saturation, Mg/K and K/Mg. In the case study, forest plantation has eliminated 88% of the native species of the moor and has decreased the coverage of the 5 species that still remain there. The variable soil properties, such as the type of elements and exchange, are very similar between the two sites, due to the availability of water and nutrients that P. patula has in the study area. This research serves as input to take technical and management measures applicable to the Colombian paramos.